Chemical and biological properties of honey from Thai stingless bee (Tetragonula leaviceps) - Kornkanok Suntiparapop (2018)
Honey from stingless bees (Tetragonula laeviceps) was collected from Chantaburi and Trat provinces in Thailand where bees are kept for commercial honey production. The honey was studied for its physiochemical, antimicrobial and antioxidant properties. For physiochemical analysis, compared to Apis mellifera honey, the honey samples collected from stingless bees were significantly greater in total moisture amount (26.98 ± 0.23 g/100g), ash content (0.26 ± 0.04 g/100g), pH (3.62 ± 0.01), total acidity (81.37 ± 0.55 meq/kg), electrical conductivity (0.62 ± 0.00 mS/cm), and HMF (1.08 ± 0.13 ppm), but no diastase activity could be detected. The sum of fructose and glucose was lower than 65% g/100g standards of A. mellifera honey, but sucrose was much higher. An agar well diffusion method was used to determine antimicrobial activities of the honey against fourteen species of bacteria (Klebsiella pneumoniae, Listeria monocytogenes, Micrococcus luteus, Proteus mirabilis, Pseudomonas aeruginosa, Staphylococcus epidermidis, Streptococcus pyogenes, methicillin-resistant Staphylococcus aureus (MRSA), Serratia marcescens, Salmonella typhimurium, Bacillus cereus, Escherichia coli, Staphylococcus aureus, and Propionibacterium acnes) and two species of yeasts (Candida albicans and Saccharomyces cerevisiae). The honey was found to inhibit the growth of thirteen species of bacteria except P. acnes and the two species of yeasts. The broth micro dilution method was used to assess the minimum inhibitory concentration (MIC) of stingless bee honey. The scavenging activity of honey samples was determined by 2, 2-diphenylpicrylhydrazyl (DPPH). It was found that the IC50in the honey samples from Chantaburi and Trat province were 0.07 ± 0.01 and 0.04 ± 0.00 mg/ml, respectively. © IBRA 2012.